Determining the optimal reliability of an electronic device from a corrective maintenance aspect - Dušan Korolija (Vojnotehnički Glasnik, 1999)
The paper presents a method for determining the optimal reliability of an electronic device from a corrective maintenance aspect. The basis of this method is the generation of reliability variants and, for each of them, the calculation of corrective maintenance criteria, and costs of reliability development and production. A corrective maintenance delay is the constraint in optimization. An example of reliability optimisation of a hypothetical electronic device is presented.